2014
DOI: 10.1186/s12913-014-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of drugs and procedures of care in the Italian hospice and hospital settings: the final three days of life for cancer patients

Abstract: BackgroundA palliative approach at the end of life typically involves forgoing certain drugs and procedures and starting others - weighing burden against potential benefit. An assessment of the palliative approach may be undertaken by investigating which drugs and procedures are used in the dying phase, and at what frequencies.MethodsDrugs were classified as potentially (in)appropriate based on expert classification. Procedures were classed as therapeutic or diagnostic. 271 consecutive cancer deaths from acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
6
0
4
Order By: Relevance
“…This likely indicates that more symptomatic patients are referred to inpatient care in the EOL phase, and may not represent a difference in the management of dyspnoea in the different care settings (referral bias). A previous study reported pronounced differences in the use of opioids, midazolam, haloperidol and drugs against pulmonary secretion between hospitals and palliative care inpatient units in the final three days of life [14]. Our population-based data from more than 40,000 cancer patients substantiate these earlier findings and highlight systematic differences in PRN prescriptions between specialised palliative care and hospitals.…”
Section: Discussionsupporting
confidence: 85%
“…This likely indicates that more symptomatic patients are referred to inpatient care in the EOL phase, and may not represent a difference in the management of dyspnoea in the different care settings (referral bias). A previous study reported pronounced differences in the use of opioids, midazolam, haloperidol and drugs against pulmonary secretion between hospitals and palliative care inpatient units in the final three days of life [14]. Our population-based data from more than 40,000 cancer patients substantiate these earlier findings and highlight systematic differences in PRN prescriptions between specialised palliative care and hospitals.…”
Section: Discussionsupporting
confidence: 85%
“…en un estudio en el que comparaban la administración de fármacos y la realización de pruebas diagnósticas y terapéuticas en los últimos tres días de vida a pacientes oncológicos ingresados en hospitales de agudos frente a centros de cuidados paliativos (hospice). La realización de gasometría arterial, radiografía simple, ecografía y TC fue significativamente mayor en los hospitales, donde los pacientes tenían tres veces más probabilidades de que se le realizara uno o más estudios diagnósticos 4 .…”
Section: Discussionunclassified
“…Por dicho motivo se incluyó en el diseño del estudio el análisis del número de extracciones de sangre en las últimas 48 horas de vida del paciente, objetivándose que ocurre en casi la mitad de los casos analizados. En el estudio de West y cols., al 16,7 % de los pacientes oncológicos ingresados en hospitales de agudos se les realizó gasometría arterial en los últimos tres días de vida4 .…”
unclassified
“…Conversely, the percentage of invasive procedures, such as X-ray, ultrasound, ECG, and nuclear medicine tests, showed an increase at EoL. From a methodological point of view, we adapted Yabroff’s [ 22 ] timeframe definitions (M12/9 and M3/0), interpreting M12/9 as the “continuous care phase” and M3/0 as the “EoL phase.” We acknowledge, however, that it is quite difficult to make any direct comparison with other studies on costs at EoL due to the different timeframes adopted (i.e., 3 days [ 23 ], 7 days [ 24 ], or 30 days [ 14 ] before death).…”
Section: Discussionmentioning
confidence: 99%